Belgian Consensus Recommendations to Prevent Vitamin K Deficiency Bleeding in the Term and Preterm Infant - Simon Fiesack (MDPI AG, 2021)
Neonatal vitamin K prophylaxis is essential to prevent vitamin K deficiency bleeding (VKDB) with a clear benefit compared to placebo. Various routes (intramuscular (IM), oral, intravenous (IV)) and dosing regimens were explored. A literature review was conducted to compare vitamin K regimens on VKDB incidence. Simultaneously, information on practices was collected from Belgian pediatric and neonatal departments. Based on the review and these practices, a consensus was developed and voted on by all co-authors and heads of pediatric departments. Today, practices vary. In line with literature, the advised prophylactic regimen is 1 or 2 mg IM vitamin K once at birth. In the case of parental refusal, healthcare providers should inform parents of the slightly inferior alternative (2 mg oral vitamin K at birth, followed by 1 or 2 mg oral weekly for 3 months when breastfed). We recommend 1 mg IM in preterm <32 weeks, and the same alternative in the case of parental refusal. When IM is perceived impossible in preterm <32 weeks, 0.5 mg IV once is recommended, with a single additional IM 1 mg dose when IV lipids are discontinued. This recommendation is a step towards harmonizing vitamin K prophylaxis in all newborns.